EVALUASI STATUS GIZI PEREMPUAN PESISIR DESA REBO KABUPATEN BANGKA - Fika Dewi Pratiwi; Sudirman Adibrata; Wahyu Adi (JFMR (Journal of Fisheries and Marine Research), 2021)
Women have an important role in the coastal community's family. The nutritional status of adult women is one of the determinants of the birth of a qualified national generation. Nutritional status can be analyzed by the BMI value, which is influenced by internal and external factors. This study aimeed to analyze the nutritional status of adult women on the coast of Rebo Village, Bangka Regency and to analyze the factors affecting the nutritional status of adult women on the coast of Rebo Village, Bangka Regency related to socio-economic conditions (income level, education level, daily activities).  This field research was conducted in May-August 2020. The research sample was determined by purposive sampling, 120 female respondents who came from different hamlets in Rebo village. Collecting data on nutritional status and socio-economic conditions using a closed questionnaire. The BMI value showed that 72 adult women have ideal body weight, while 48 people were not ideal. The results of the chi-square analysis showed that the level of education and the level of activity have an influence on the BMI value of adult women, while the income level does not affect the BMI value. Further research can be carried out by examining the dietary consumption patterns and health status of adult women. The results obtained can be used as a basis for making policies or programs to improve the welfare of coastal families in Rebo village, which have an impact on the ability to access the variety and quality of daily food.